Incidences and factors associated with perioperative cardiac arrest in trauma patients receiving anesthesia - Siriphuwanun V; Punjasawadwong Y; Saengyo S; Rerkasem K (Dove Medical Press, 2018)
Visith Siriphuwanun,1 Yodying Punjasawadwong,1 Suwinai Saengyo,2 Kittipan Rerkasem2,3 1Department of Anesthesiology, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 2Non-communicable Disease Center of Excellence and Department of Surgery, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 3Non-communicable Disease Center of Excellence, Research Institute for Health Sciences, Chiang Mai University, Chiang Mai, Thailand Purpose: The aim of this study was to determine the incidences and factors associated with perioperative cardiac arrest in trauma patients who received anesthesia for emergency surgery.Patients and methods: This retrospective cohort study was approved by the medical ethical committee, Faculty of Medicine, Maharaj Nakorn Chiang Mai Hospital, Thailand. Data of 19,683 trauma patients who received anesthesia between January 2007 and December 2016, such as patient characteristics, surgery procedures, anesthesia information, anesthetic drugs, and cardiac arrest outcomes, were analyzed. Data of patients receiving local anesthesia by surgeons or monitoring anesthesia care (MAC) and those with much information missing were excluded. Factors associated with perioperative cardiac arrest were identified using univariate analysis and the multiple regression model. A stepwise algorithm was chosen at a P-value of <0.20 which was selected for multivariate analysis. A P-value of <0.05 was concluded as statistically significant.Results: The perioperative cardiac arrest in trauma patients receiving anesthesia for emergency surgery was 170.04 per 10,000 cases. Factors associated with perioperative cardiac arrest in trauma patients were as follows: age >65 years (risk ratio [RR] =1.41, CI =1.02–1.96, P=0.039), American Society of Anesthesiologist (ASA) physical status 3 or higher (ASA physical status 3–4, RR =4.19, CI =2.09–8.38, P<0.001; ASA physical status 5–6, RR =21.58, CI =10.36–44.94, P<0.001), sites of surgery (intracranial, intrathoracic, upper intra-abdominal, and major vascular, each P<0.001), cardiopulmonary comorbidities (RR =1.55, CI =1.10–2.17, P=0.012), hemodynamic instability with shock prior to receiving anesthesia (RR =1.60, CI =1.21–2.11, P<0.001), and having a history of alcoholism (RR =5.27, CI =4.09–6.79, P<0.001).Conclusion: The incidence of perioperative cardiac arrest in trauma patients receiving anesthesia for emergency surgery was very high and correlated with patient’s factors, especially old age and cardiopulmonary comorbidities, a history of drinking alcohol, increased ASA physical status, hemodynamic instability with shock prior to surgery, and sites of surgery such as brain, thorax, abdomen, and the major vascular region. Anesthesiologists and surgeons should be aware of a warning system and a well-equipped track to manage the surgical trauma patients. Keywords: anesthesia, emergency surgery, incidence, perioperative cardiac arrest, risk factor, trauma patients, cardiac arrest in trauma patients receiving anesthesia